The reality of reflective practices in action research and its difficulties from the point of view of a random sample of primary school teachers at Umm Al-Muminin Aisha School in Al-Zulfi Governorate - Al-Fahd, Lulwah Abdullah; Al-Arfaj, Abeer Mohammed (Journal of Educational and Psychological Sciences, 2023)
This study aimed to explore the reflective teaching practices that teachers do while conducting their action research. Multiple interviews with five elementary school teachers- chosen randomly- in Alzulfy region in Saudi Arabia was used as a tool to collect data. These interviews focused on three parts of reflective teaching practices: objectives, contents, and assessments. Regarding the objectives part, teachers tended to ensure that the objectives were aligned with their research titles. In the content part, teachers focused on using variety of tools to collect data, connecting the research problems to their effects on the educational field, and using students’ portfolio. Moreover, teachers tended to meet with their colleagues to discuss their reflective practices regarding the assessment part. Additionally, obstacles that teachers faced while implanting reflective practices in their teaching consisted of shortages of logistic supports, and weakness in teachers’ research skills and academic writing. They also expressed their needs for training in reflective thinking and collaborating in choosing research problems. Therefore, this study recommended providing workshops for teachers to strengthen their reflective practices and their abilities to write about them academically. Also, it suggested providing guidance for action research showing the reflective practices that teachers need to follow. Keywords: reflective practices in teaching, action research, elementary school teachers, supervised practices.